The Role of Islamic Education In Indonesia's Socio-Politics in The Digital Era - Hamdi Hidayat; Muhtadi Abdul Mun’im (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
This research discusses the role of Islamic education in the context of Indonesia's social and political landscape in the digital era, characterized by advancements in information and communication technology. The introduction explains that the digital era has transformed the way social interactions occur and information is disseminated, bringing challenges and opportunities for society, especially the youth. The research methodology employed is a qualitative approach using library research, which includes a literature analysis related to the theme of Islamic education and its impact on social and political morals and ethics. The findings indicate that Islamic education serves as a tool for building the character and morals of students while also providing critical political and social awareness.